In the past, winter was winter, and summer was summer: Climate change in the eyes of older adults from Poland - Budziszewska, Magdalena (Quaestiones Geographicae, 2024)
Older adults have a long-time perspective when it comes to the perception of changes in local climate and are uniquely vulnerable to these developments in terms of health. The discussed in-depth, qualitative study is based on interviews with people from the age group over 65 years (N = 10; five females), who live in different regions of Poland, concerning their views on climate change and its mitigation. Reflexive thematic analysis was used to create a map of their observations and attitudes. Results indicate the importance of perceiving climate change in specific and local categories as well as show frequent identification of this issue with traditional environmentalism focussed on pollution and littering. This foregrounds difficulties in understanding invisible greenhouse gases and how they work. In terms of mitigation, the study has revealed little faith in climate action undertaken by fellow citizens and the government, as well as a sense of limited agency, which is also disproportionally projected onto children and young adults. However, through everyday observations, older adults appear to be profoundly aware of how climate change impacts the environment. Contrary to stereotypes, they also declare high emotional engagement in this issue. Consequently, despite being overlooked with respect to this subject, older adults can play an important role in promoting climate awareness and climate-friendly policies.